In vitro studies on the cytotoxicity, elastase, and tyrosinase inhibitory activities of tomato (Solanum lycopersicum Mill.) extract - Neneng Siti Silfi Ambarwati; Mari Okatini Armandari; Wahyu Widayat; Yesi Desmiaty; Berna Elya; Ayun Erwina Arifianti; Islamudin Ahmad (Wolters Kluwer Medknow Publications, 2022)
Tomatoes (Solanum lycopersicum Mill.), a common vegetable in Indonesia, contain high levels of lycopene, which is good for the body. This research further investigates the activity of polar and nonpolar fractions of tomatoes as elastase and tyrosinase inhibitory, and cytotoxic agents. The extraction procedure used is maceration, fractionation through liquid-liquid fractionation, purification of phytochemical substances is achieved through the application of thin layer chromatography. Elastase and tyrosinase inhibitory activity was analyzed using spectrophotometry and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide cytotoxic assay. The result showed that the extract yield was 0.004%. The percentage of polar fraction from the extract was 2.58%, while the nonpolar fraction was 0.69%. The elastase inhibitory activity of polar and nonpolar fractions of tomato extract is 87.21% ± 7.57% and 73.12% ± 7.44%, respectively, The elastase inhibitory activity of polar and nonpolar fractions of tomato extract is 87.21% ± 7.57% and 73.12% ± 7.44%, respectively. The fractions had higher the anti-elastase activity than the positive control quercetin (65.97% ± 3.00%). The tyrosinase inhibitory activity of polar and nonpolar fractions of tomato extract is 23.71% ± 7.91% and 41.16% ± 5.41% (kojic acid as standard is 65.07% ± 0.86%), respectively. The IC50 of the cytotoxic assay to NIH 3T3 mouse embryonic fibroblast cells of the polar and nonpolar fraction of tomato extract is 1820.90 μg/mL and 1643.86 μg/mL, respectively.